Obsessed: Sebuah Analisa Plot - Febby Pratama; Laila Desnaranti (LITERATUS, 2022)
One of the most popular forms of entertainment worldwide is the movie. As is common knowledge, most individuals enjoy movies. One of the literary forms is the movie, which appeals to viewers with its imaginative visuals and audio. People get more knowledge from watching movies, whether they do it at home or in theaters. It is one of the literary genres that is written with stage production in mind. The discussion between all of the characters gives the plot expression. The author's blueprint for the events in the novel is called the plot. Preliminary Exposition, Starting Point, Rising Action, Climax, Falling Action, and Ending are the steps for plot analysis. People will learn about all of the depictions of the events in the story through the plot. The story "Obsessed" has a straightforward plot. Derek, Sharon, and Lisa are the three main protagonists in this film. Since Lisa won't be a hindrance to Derek's family's happiness, the story has a happy ending.